Efectos de la Responsabilidad Social Empresarial (RSE) en la Rentabilidad de las Cooperativas de Ahorro y Crédito del segmento 1 del Ecuador, periodos 2021-2023. - González Coronel, Ximena Alexandra (2025)
Corporate Social Responsibility (CSR) is a topic of transcendental importance for any type of organization that needs to remain sustainable over time, therefore, the objective of this document is to evaluate the effects of Corporate Social Responsibility (CSR) on the Profitability of Savings and Credit Cooperatives in segment 1 of Ecuador, periods 2021-2023, to achieve this goal, the following methodological process was considered, made up of a mixed approach, of a descriptive type, of a correlational scope, likewise, the analytical-synthetic, inductive and deductive methods were used, as the main statistical method, the Pearson Correlation Coefficient and a scatter diagram were used. The main result indicates that, in general, there is an average correlation coefficient of 0.34. This data indicates that a low positive correlation level was detected between the CSR variables and profitability of the COACs of segment 1. Within this result, the dimensions stand out: P3 Economic participation of members with an average value of 0.47 (moderate positive correlation), and the dimension P5 Education, training and information with an average coefficient of 0.49 (moderate positive correlation). The main conclusion is that the existence of a relationship or effect between CSR and financial profitability is due to several factors linked to the social and community principle, focus on the well-being of members and the cooperative model managed by the COACs, which helps to create trust and a favorable perception of members.